2021
DOI: 10.1002/ps.6599
|View full text |Cite
|
Sign up to set email alerts
|

Recent applications of chromatography for analysis of contaminants in cannabis products: a review

Abstract: In the last few years, the cultivation of cannabis has been increasing due to greater use in foods, recreational use, creams, oils, and other applications. Thus, analysis of contaminants (e.g. pesticides and mycotoxins) in cannabis products is necessary to ensure consumer safety. This review is focused on the analytical procedures, based on chromatographic techniques, used for the determination of contaminants in cannabis and related products, developed from 2015 to 2020. QuEChERS (acronym of quick, easy, chea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For fiber hemp, seed treatment with conventional fungicides reduced incidence of damping-off caused by F. solani (Mishra, 1987). Pesticide residues are particularly important in C. sativa grown for medical purposes, but the low number of products approved for disease control, the continued use of control methods that evolved when the plant was illegal, and the lack of scrutiny normally provided by the food and drug approval process (Seltenrich, 2019;Pinkhasova et al, 2021) have resulted in illegal pesticide residues being commonly found in Cannabis products (Narváez et al, 2020;López-Ruiz et al, 2021). Health Canada maintains a nationwide program that couples unannounced inspections and targeted testing to monitor pesticide use and reduce the potential risk to public health (Health Canada, 2019), whereas in the USA, residues are regulated on a state-by-state basis.…”
Section: Disease Controlmentioning
confidence: 99%
“…For fiber hemp, seed treatment with conventional fungicides reduced incidence of damping-off caused by F. solani (Mishra, 1987). Pesticide residues are particularly important in C. sativa grown for medical purposes, but the low number of products approved for disease control, the continued use of control methods that evolved when the plant was illegal, and the lack of scrutiny normally provided by the food and drug approval process (Seltenrich, 2019;Pinkhasova et al, 2021) have resulted in illegal pesticide residues being commonly found in Cannabis products (Narváez et al, 2020;López-Ruiz et al, 2021). Health Canada maintains a nationwide program that couples unannounced inspections and targeted testing to monitor pesticide use and reduce the potential risk to public health (Health Canada, 2019), whereas in the USA, residues are regulated on a state-by-state basis.…”
Section: Disease Controlmentioning
confidence: 99%
“…Cannabis is a hyperaccumulator; therefore, trace contamination of biomass is an issue when grown next to other crops (McPartland and McKernan 2017 ; Wu et al 2021 ). For example, hemp grown in proximity to other commodity crops can be contaminated by pesticides from those adjacent fields (López-Ruiz et al 2022 ). This becomes problematic when the pesticides used are not accepted by commercial cannabis regulations and drift to the hemp crop.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to develop a benchtop-scale HPLC method for separating 11 pesticides and 26 cannabinoids, and evaluate the theoretical suitability of the method for separating pesticides and cannabinoids from six industrial hemp processing matrices using preparative-scale liquid chromatography (PLC). Methods for both cannabinoid and pesticide quantitation have been reported using HPLC, but targeted pesticide separation and assay for scale-up to PLC has not been reported (Craven et al 2019 ; Atapattu and Johnson 2020 ; López-Ruiz et al 2022 ). Using a benchtop-scale HPLC adds an element of novelty to this work by incorporating principles of green chemistry for developing preparative-scale liquid chromatography methods of interest to the broader industrial community.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of this study was to investigate whether the cannabis extract obtained from cannabis flowers that contain the maximum allowed level of mycotoxins affects human safety and health. There are many recently published manuscripts related to quantification techniques for the determination of mycotoxins in cannabis flower and cannabis extracts, inapplicable for the equipment we used ( 21 , 22 ). For that reason, a novel LC/MS/MS method was developed and validated for the determination of aflatoxins and OchA in cannabis extracts to demonstrate that this analytical method is suitable for the intended experimental design, thus, achieving the set goal.…”
Section: Introductionmentioning
confidence: 99%